Estudio experimental de la radiación global ultravioleta en San Jose, Costa Rica (ING) - Wright, Jaime (1996)
The ultraviolet global radiation and the global solar radiation at San José, Costa Rica (latitude: 9°56´, longitude: 84°54´, altitude: 1.172m.) during the period October 1993 to January 1995 were analyzed with respect to their seasonal variations and their interdependence. The dependence between the ultraviolet radiation and the clearness index of the skies was also investigated. A poor correlation was found between the quotient of the ultraviolet radiation and the global solar radiation (Hv/Hg) and between the global solar radiations and the extraterrestrial solar radiation (Hg/Ho). The correlation coefficient found between Hv/Hg and Hg/Ho was not greater than 0, 25 for four categories of clearness index; i.e., covered skies, clear skies, and two intermediate conditions. This demonstrates that the ultraviolet radiation is not only associated with the clearness of the skies, but also with other atmospheric transmission conditions. A regression analysis between the hourly values of the ultraviolet and global radiation yielded a linear relationship with a determination coefficient greater than 98%. Thus a simple linear regression is reliable for the estimation of the ultraviolet radiation in San José from global solar radiation data.